ANALISIS PENDAPATAN TERHADAP EKONOMI MASYARAKAT NELAYAN PESISIR PANTAI DI DESA SUNGAI DURI KABUPATEN BENGKAYANG - Maulana, Candra; Mashudi, Mashudi; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the influence of income on the economic conditions of fishing communities on the coast of Sungai Duri I Village, Bengkayang Regency. Fishermen are a community group that relies on marine products as their primary source of livelihood. However, fluctuations in catches, weather, and access to production facilities often affect the stability of their income. The method used in this study is a qualitative approach with data collection techniques through field observations and in-depth interviews. Data were analyzed using surveys, interviews, and documentation to examine the relationship between income and economic indicators of fishing communities, such as consumption levels, education, and access to health services. The results show that fishermen's income has a significant influence on improving family economic conditions, although there are still structural obstacles that need to be addressed. It is hoped that the results of this study can be used as a consideration for local governments in designing more effective fishermen empowerment policies.